2010
DOI: 10.1177/0961203310361488
|View full text |Cite
|
Sign up to set email alerts
|

Some antiphospholipid antibodies bind to various serine proteases in hemostasis and tip the balance toward hypercoagulant states

Abstract: The body has an elaborate system that maintains blood circulation and rapidly stops bleeding when vessels are damaged. Abnormalities that disrupt this balance may lead to thrombosis. While beta(2)-glycoprotein I is generally accepted as the major antigen for antiphospholipid antibodies in the antiphospholipid syndrome, our accumulated studies show that some antiphospholipid antibodies bind homologous enzymatic domains of several serine proteases involved in hemostasis and fibrinolysis. Functionally, some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, we found that monoclonal antibodies generated from DENV-immunised mice can cross-react with human Plg and enhance its activation (12). It is known that plasmin (Plm) and thrombin share homologous trypsin/thrombin-like serine protease domains (13) and that some mAbs generated from patients with antiphospholipid syndrome (APS) can bind various serine proteases including Plg and thrombin and tip the balance toward a hypercoagulant state (13)(14)(15)(16)(17). Therefore, we hypothesised that some anti-Dengue antibodies may bind to thrombin and inhibit its activity to thus promote haemorrhage in patients infected with DENV.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that monoclonal antibodies generated from DENV-immunised mice can cross-react with human Plg and enhance its activation (12). It is known that plasmin (Plm) and thrombin share homologous trypsin/thrombin-like serine protease domains (13) and that some mAbs generated from patients with antiphospholipid syndrome (APS) can bind various serine proteases including Plg and thrombin and tip the balance toward a hypercoagulant state (13)(14)(15)(16)(17). Therefore, we hypothesised that some anti-Dengue antibodies may bind to thrombin and inhibit its activity to thus promote haemorrhage in patients infected with DENV.…”
Section: Introductionmentioning
confidence: 99%
“…10 Antiphospholipid antibodies were shown to interact with endothelial cells, monocytes and platelets converting them into a prothrombotic state and to inhibit several natural anticoagulants like activated protein C, prothrombin/thrombin and plasmin. 11,12 Pregnancy itself can act as a second hit, therefore it is possible that, during gestation, multiple thrombotic events can damage placental blood flow and impair the placental development. In fact, multiple placental infarcts have been described in pregnancies complicated with aPL.…”
Section: The First Year Of Lifementioning
confidence: 99%
“…Thus, we could assume that the pathogenesis of perinatal thrombosis associated with aPL can be explained by both the transplacental passage of maternal antibodies and the possible de novo synthesis of IgM and IgG aPL in the fetus and newborn. 739…”
Section: Neonatal Thrombosis and Antiphospholipid Antibodiesmentioning
confidence: 99%
“…These antibodies bind to phospholipids and protein epitopes found in cardiolipin, annexin V, prothrombin and β-2 glycoprotein-1 [24]. The antiphospholipid antibodies that recognize epitopes on β-2 glycoprotein-1 also bind serine proteases involved in hemostasis and fibrinolysis and hence promote thrombosis [79].…”
Section: Hypercoagulabilitymentioning
confidence: 99%
“…Tissue factor pathway inhibitor activity is reduced in SLE and this is associated with increased levels of tissue factor and subsequent hypercoagulability [82]. Antiphospholipid antibodies bind to components of the coagulation cascade and activate the coagulation system leading to a procoagulant state along with decreased fibrinolysis via reducing activity of tPA [79][80][81].…”
Section: Hypercoagulabilitymentioning
confidence: 99%